Effect of Prone Positioning With Individualized Positive End-Expiratory Pressure in Acute Respiratory Distress Syndrome Using Electrical Impedance Tomography - Mi, Liangyu; Chi, Yi; Yuan, Siyi; He, Huaiwu; Long, Yun; Frerichs, Inéz; Zhao, Zhanqi (Frontiers in Physiology, 2022)
Background: Positive end-expiratory pressure (PEEP) optimization during prone positioning remains under debate in acute respiratory distress syndrome (ARDS). This study aimed to investigate the effect of prone position on the optimal PEEP guided by electrical impedance tomography (EIT). Methods: We conducted a retrospective analysis on nineteen ARDS patients in a single intensive care unit. All patients underwent PEEP titration guided by EIT in both supine and prone positions. EIT-derived parameters, including center of ventilation (CoV), regional ventilation delay (RVD), percentage of overdistension (OD) and collapse (CL) were calculated. Optimal PEEP was defined as the PEEP level with minimal sum of OD and CL. Patients were divided into two groups: (1) Lower Optimal PEEPPP (LOP), where optimal PEEP was lower in the prone than in the supine position, and (2) Not-Lower Optimal PEEPPP (NLOP), where optimal PEEP was not lower in the prone compared with the supine position. Results: Eleven patients were classified as LOP (9 [8-9] vs. 12 [10-15] cmH2O; PEEP in prone vs. supine). In the NLOP group, optimal PEEP increased after prone positioning in 4 patients and remained unchanged in the other 4 patients. Patients in the LOP group had a significantly higher body mass index (26 [25-28] vs. 22 [17-25] kg/m2; p = 0.009) and lower ICU mortality (0/11 vs. 4/8; p = 0.018) compared with the NLOP group. Besides, PaO2/FiO2 increased significantly during prone positioning in the LOP group (238 [170-291] vs. 186 [141-195] mmHg; p = 0.042). CoV and RVD were also significantly improved during prone positioning in LOP group. No such effects were found in the NLOP group. Conclusions: Broad variability in optimal PEEP between supine and prone position was observed in the studied ARDS patients. Not all patients showed decreased optimal PEEP during prone positioning. Patients with higher body mass index exhibited lower optimal PEEP in prone position, better oxygenation and ventilation homogeneity.